Positive electrode active material, preparation method thereof, positive electrode including the positive electrode active material, and lithium secondary battery
A lithium nickel-manganese-aluminum composite oxide with a coated aluminum layer addresses the cobalt scarcity issue by enhancing stability and efficiency in lithium secondary batteries, achieving high capacity and long life under demanding conditions.
Patent Information
- Application Number
- JP2024094852
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-12
- Filing Date
- 2024-06-12
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-06-12
AI Technical Summary
The increasing demand for large-sized, high-capacity lithium secondary batteries has highlighted the scarcity and high cost of cobalt, necessitating the development of positive electrode active materials that either exclude cobalt or have reduced cobalt content while maintaining high capacity, stability, and efficiency.
A lithium nickel-manganese-aluminum composite oxide with a specific nickel and aluminum content is coated with a thin, uniform aluminum layer to form a core-shell structure, enhancing structural stability and reducing side reactions under high voltage and temperature conditions.
The solution minimizes production costs, maximizes capacity, and improves high voltage and high temperature characteristics, ensuring long life characteristics for lithium secondary batteries.
Smart Images

Figure 2024178142000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a positive electrode active material, a method for producing the same, a positive electrode containing the same, and a lithium secondary battery. [Background technology]
[0002] Lithium secondary batteries, which have high energy density and are easy to carry, are mainly used as the driving power source for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, active research has been conducted on using high-energy-density lithium secondary batteries as driving power sources or power storage sources for hybrid and electric vehicles.
[0003] In order to realize lithium secondary batteries that meet these applications, various positive electrode active materials have been studied. Among them, lithium nickel oxide, lithium nickel manganese cobalt composite oxide, lithium nickel cobalt aluminum composite oxide, lithium cobalt oxide, etc. are mainly used as positive electrode active materials. However, in recent years, while the demand for large-sized, high-capacity, or high-energy density lithium secondary batteries has rapidly increased, the supply of positive electrode active materials containing the rare metal cobalt is expected to be extremely short. In other words, since cobalt is expensive and there are not many remaining reserves, it is necessary to develop positive electrode active materials that do not contain cobalt or have a reduced cobalt content. Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention provides a positive electrode active material containing a lithium nickel-manganese-aluminum composite oxide, which ensures economical efficiency, high capacity, and long life characteristics, and has improved high voltage characteristics and high temperature characteristics, a method for producing the same, and a positive electrode and a lithium secondary battery containing the same. [Means for solving the problem]
[0005] In one embodiment of the present invention, there is provided a positive electrode active material comprising core particles containing a lithium nickel-manganese-aluminum composite oxide, and a coating layer containing aluminum located on the surface of the core particles, wherein the nickel content of the core particles is 60 mol % to 80 mol %, the aluminum content of the core particles is 1 mol % to 3 mol %, and the aluminum content of the coating layer is 0.1 mol % to 2 mol %, relative to 100 mol % of all metals excluding lithium.
[0006] In another embodiment of the present invention, there is provided a method for producing a positive electrode active material, comprising: mixing a nickel-manganese-aluminum-based composite hydroxide and a lithium raw material; performing a first heat treatment to obtain a lithium nickel-manganese-aluminum-based composite oxide; introducing the obtained lithium nickel-manganese-aluminum-based composite oxide into a solution in which an aluminum raw material is mixed in an aqueous solvent; mixing the resulting mixture; drying; and performing a second heat treatment to obtain a positive electrode active material, wherein the nickel-manganese-aluminum-based composite hydroxide has a nickel content of 60 mol % to 80 mol % and an aluminum content of 1 mol % to 3 mol % relative to 100 mol % of all metals in the positive electrode active material, and the aluminum content in the aluminum raw material is 0.1 mol % to 2 mol % relative to 100 mol % of all metals in the positive electrode active material excluding lithium.
[0007] In yet another embodiment of the present invention, a positive electrode is provided that includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above.
[0008] In yet another embodiment of the present invention, there is provided a lithium secondary battery comprising the positive electrode, the negative electrode, and an electrolyte. Effect of the Invention
[0009] The positive electrode active material according to an embodiment of the present invention minimizes production costs and maximizes capacity, while ensuring long life characteristics and improving high voltage and high temperature characteristics. A lithium secondary battery using the positive electrode active material can achieve long life characteristics by exhibiting high initial charge / discharge capacity and efficiency even under high voltage driving conditions. [Brief description of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view illustrating a lithium secondary battery according to an embodiment. [Diagram 2] 1 is a scanning electron microscopy (SEM) image of the positive electrode active material of Comparative Example 1. [Diagram 3] 1 is a SEM image of the positive electrode active material of Comparative Example 2. [Figure 4] 1 is a SEM-EDS (Scanning Electron Microscopy-Electron Dispersive X-ray Spectroscopy) image of a cross section of the positive electrode active material of Example 1. [Diagram 5] 1 is a SEM-EDS image of a cross section of the positive electrode active material of Example 2. [Figure 6] 1 is a SEM-EDS image of a cross section of the positive electrode active material of Example 3. [Figure 7] 1 is a SEM-EDS image of a cross section of the positive electrode active material of Example 4. [Figure 8] 13 is a SEM-EDS image of a cross section of the positive electrode active material of Comparative Example 3. [Figure 9] 13 is a SEM-EDS image of a cross section of the positive electrode active material of Comparative Example 5. [Figure 10] 13 is an SEM image of the surface of the positive electrode active material of Comparative Example 5. [Figure 11] 1 is a depth profile of TOF-SIMS (Time-of-Flight Secondary Ion Mass Spectrometry) for the positive electrode active material of Example 1. [Figure 12]1 is a transmission electron microscopy (TEM) image of a cross section of a positive electrode active material of Example 1. [Figure 13] This is an enlarged TEM image of the area indicated by the square in FIG. [Figure 14] This is an image of an EDS analysis performed on the TEM image in Figure 13, with O, Al, Mn, and Ni highlighted from the left. [Figure 15] 15 is an EDS line profile showing the change in the content of O, Al, Mn, and Ni in the direction of the arrow shown in FIG. 13 and FIG. 14. [Figure 16] 3 shows a TEM image and a TEM-EDS analysis image of a cross section of the positive electrode active material of Example 1. [Figure 17] 17 is an EDS line profile showing the change in the content of O, Al, Mn, and Ni in the direction of the arrow shown in FIG. 16. [Figure 18] 1 is a TEM image of a cross section of a positive electrode active material of Example 1. [Figure 19] An enlarged photograph (left) of Area 1 in Figure 18 and an image (right) highlighting aluminum by EDS analysis. [Figure 20] An enlarged photograph (left) and an EDS analysis image (right) of Area 2 in FIG. [Figure 21] An enlarged photograph (left) and an EDS analysis image (right) of Area 3 in FIG. [Figure 22] 4 is a TEM-EDS image obtained by enlarging and analyzing a primary particle located at the outermost shell of a secondary particle in a cross section of a positive electrode active material of Example 1. [Figure 23] 23 shows TEM images of the areas indicated by the arrows (1) to (6) in FIG. 22. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention is not limited to the embodiments described herein, but may be embodied in various different forms.
[0012] The terms used herein are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless otherwise clearly indicated in the context.
[0013] As used herein, "combinations thereof" refers to mixtures, laminates, composites, copolymers, alloys, blends, reaction products, and the like of compositions.
[0014] It should be understood that the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.
[0015] In the drawings, the thickness of the various layers and regions is exaggerated for clarity, and similar parts are designated by the same reference numerals throughout the specification. When a part such as a layer, film, region, plate, etc. is said to be "on" or "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part between them. Conversely, when a part is said to be "directly on" another part, it means that there is no other part between them.
[0016] Further, the term "layer" as used herein includes not only a shape formed on the entire surface when observed in a plan view, but also a shape formed on a portion of the surface.
[0017] The average particle size can be measured by a method well known to those skilled in the art, for example, by using a particle size analyzer or by using a transmission electron microscope image or a scanning electron microscope image. Alternatively, the average particle size can be obtained by measuring using a dynamic light scattering method, counting the number of particles for each particle size range by performing data analysis, and then calculating the average particle size value. Unless otherwise defined, the average particle size means the diameter (D50) of particles whose cumulative volume is 50% by volume in the particle size distribution. In addition, unless otherwise defined, the average particle size can be obtained by measuring the size (diameter or major axis length) of 20 or more particles randomly from a scanning electron microscope image to obtain a particle size distribution, and taking the diameter (D50) of particles whose cumulative volume is 50% by volume in the particle size distribution as the average particle size.
[0018] Here, "or" is not to be construed in an exclusive sense, for example "A and / or B" is to be construed as including A, B, A+B, etc.
[0019] The term "metal" is interpreted as including general metals, transition metals, and metalloids (semimetals).
[0020] positive electrode active material In one embodiment of the present invention, there is provided a positive electrode active material comprising core particles containing a lithium nickel-manganese-aluminum composite oxide, and a coating layer containing aluminum located on the surface of the core particles, in which the nickel content of the core particles is 60 mol % to 80 mol %, the aluminum content of the core particles is 1 mol % to 3 mol %, and the aluminum content of the coating layer is 0.1 mol % to 2 mol %, relative to 100 mol % of all metals excluding lithium.
[0021] In recent years, the price of cobalt, a rare metal, has soared, and there is a demand for the development of positive electrode active materials that do not contain cobalt or that have a reduced content of cobalt. Among them, positive electrode active materials with an olivine crystal structure such as lithium iron phosphate (LFP), lithium manganese phosphate (LMP), and lithium manganese iron phosphate (LMFP), or a spinel crystal structure such as lithium manganese oxide (LMO), have a limited capacity due to the small lithium storage capacity that can be utilized within the structure. Layered nickel-manganese positive electrode active materials have excellent capacity and efficiency characteristics due to the high lithium storage capacity within the structure, making them suitable as materials for high-capacity batteries. However, the removal of cobalt, which plays a key role in the layered structure, reduces structural stability, increases resistance, and makes it difficult to ensure long life characteristics. In addition, the removal of cobalt accelerates side reactions between the positive electrode active material and the electrolyte under high voltage and high temperature conditions, increasing the amount of gas generated and reducing life characteristics.
[0022] In one embodiment, aluminum is introduced as a base material and a lithium nickel-manganese-aluminum composite oxide is applied to the core particles to improve structural stability and minimize production costs. A certain amount of aluminum is coated in a specific manner to form a uniform coating layer, thereby maximizing capacity and efficiency, and reducing gas generation even under high voltage and high temperature conditions to provide a positive electrode active material that can achieve long life characteristics.
[0023] Core Particles The core particles contain a lithium nickel-manganese-aluminum composite oxide.
[0024] The nickel content is 60 mol% to 80 mol% relative to 100 mol% of all metals excluding lithium in the positive electrode active material. Nickel is contained in the core particles, but a part of it can migrate to the coating layer during the coating process, and therefore the nickel content means the nickel content contained in the entire positive electrode active material. The nickel content can be, for example, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol% relative to 100 mol% of all metals excluding lithium in the positive electrode active material. When the nickel content satisfies the above range, high capacity can be achieved and structural safety can be improved even if the cobalt content is reduced.
[0025] Such composite oxides are distinguished from high-nickel composite oxides having a nickel content of more than 80 mol%. According to one embodiment, a positive electrode active material having a nickel content of 60 mol% to 80 mol% differs from a high-nickel positive electrode active material in terms of the residual lithium content on the surface, the pH condition on the surface, the surface shape, etc., and therefore the same coating method cannot be applied, and the performance and application fields are different.
[0026] The manganese content is, for example, 10 mol% to 39 mol% relative to 100 mol% of the total metals excluding lithium in the positive electrode active material, and may be 10 mol% to 35 mol%, 10 mol% to 30 mol%, 10 mol% to 29 mol%, 15 mol% to 39 mol%, 20 mol% to 39 mol%, 20 mol% to 30%, etc. Manganese is contained in the core particles, but a part of it can move to the coating layer during the coating process, so the manganese content means the manganese content contained in the entire positive electrode active material. When the manganese content satisfies the above range, the positive electrode active material can improve structural stability while achieving high capacity.
[0027] The aluminum content in the core particle is 1 mol% to 3 mol% relative to 100 mol% of the total metals excluding lithium in the positive electrode active material, and may be, for example, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%. Here, the aluminum content means the content of aluminum present in the core particle. When the aluminum content of the core particle satisfies the above range, even if the cobalt in the core particle is removed, a stable layered structure can be maintained, and the problem of the structure collapsing due to charging and discharging can be suppressed, and the long life characteristics of the positive electrode active material can be realized.
[0028] According to one embodiment, the aluminum concentration in the core particle may be uniform. That is, the aluminum concentration in the core particle may be uniformly distributed from the center to the surface, or the aluminum concentration in the core particle may not be higher or lower than that in the inside, and the aluminum may be uniformly dispersed in the core particle. This structure may be obtained by synthesizing a composite oxide using nickel-manganese-aluminum hydroxide as a precursor by using an aluminum raw material in the preparation of a precursor without further doping aluminum in the synthesis process of the core particle. The core particle may be in the form of a secondary particle in which a plurality of primary particles are aggregated, and the aluminum content in the primary particle may be the same or similar regardless of the position of the primary particle. That is, if a primary particle is selected from an arbitrary position in the cross section of the secondary particle and the aluminum content in the inside, not the interface of the primary particle, is measured, the aluminum content may be expressed as the same / similar / uniform regardless of the position of the primary particle, that is, whether the primary particle is close to the center or the surface of the secondary particle. In such a structure, even if cobalt is absent or present in only a very small amount, a stable layered structure can be maintained, no aluminum by-products or aluminum agglomerates are generated, and the capacity, efficiency, and life characteristics of the positive electrode active material can be improved simultaneously.
[0029] The lithium nickel-manganese-aluminum composite oxide is represented, for example, by the following chemical formula 1. [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1 In Chemical Formula 1, 0.9 ≦ a1 ≦ 1.8, 0.6 ≦ x1 ≦ 0.8, 0.1 ≦ y1 ≦ 0.39, 0.01 < z1 ≦ 0.03, 0 ≦ w1 ≦ 0.29, 0.9 ≦ x1 + y1 + z1 + w1 ≦ 1.1, and 0 ≦ b1 ≦ 0.1, where M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr, and X is one or more elements selected from F, P, and S.
[0030] In Chemical Formula 1, 0.9 ≦ a1 ≦ 1.5, or 0.9 ≦ a1 ≦ 1.2 may hold. Also, 0.6 ≦ x1 ≦ 0.79, 0.6 ≦ x1 ≦ 0.78, 0.6 ≦ x1 ≦ 0.75, 0.65 ≦ x1 ≦ 0.8, or 0.7 ≦ x1 ≦ 0.79, 0.1 ≦ y1 ≦ 0.35, 0.1 ≦ y1 ≦ 0.30, 0.1 ≦ y1 ≦ 0.29, 0.15 ≦ y1 ≦ 0.39, or 0.2 ≦ y1 ≦ 0.3, 0.01 < z1 ≦ 0.025, 0.01 < z1 ≦ 0.02, or 0.01 < z1 ≦ 0.019, 0 ≦ w1 ≦ 0.28, 0 ≦ w1 ≦ 0.27, 0 ≦ w1 ≦ 0.26, 0 ≦ w1 ≦ 0.25, 0 ≦ w1 ≦ 0.24, 0 ≦ w1 ≦ 0.23, 0 ≦ w1 ≦ 0.22, 0 ≦ w1 ≦ 0.21, 0 ≦ w1 ≦ 0.2, 0 ≦ w1 ≦ 0.15, 0 ≦ w1 ≦ 0.1, or 0 ≦ w1 ≦ 0.09, etc. may hold.
[0031] The lithium nickel - manganese - aluminum - based composite oxide of the core particles can be, for example, a cobalt - free compound that does not contain cobalt or contains an extremely small amount of cobalt.
[0032] The core particles can be in the form of secondary particles formed by aggregation of a plurality of primary particles. The secondary particles can be spherical, ellipsoidal, polyhedral, or irregular in shape, and the primary particles can be spherical, ellipsoidal, plate - shaped, or a combination thereof.
[0033] The core particles are susceptible to chemical attack by components in the electrolyte when the battery is operated under high voltage or high temperature conditions, and many side reactions with the electrolyte may occur, which may result in a large amount of gas generation and reduced battery life and safety. However, such problems can be solved by introducing a coating layer according to one embodiment described below.
[0034] Coating Layer The aluminum content in the coating layer is characterized by being 0.1 mol% to 2 mol% relative to 100 mol% of the total metals excluding lithium in the positive electrode active material, and may be, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. This means only the content of aluminum contained in the coating layer, apart from the aluminum contained in the core particles. The aluminum content in the coating layer can be measured, for example, by SEM-EDS analysis of the surface or cross section of the positive electrode active material. When the aluminum content in the coating layer satisfies the above range, it is possible to form a coating layer with a uniform and thin thickness, the resistance of the positive electrode active material does not increase, side reactions with the electrolyte are effectively suppressed, and the life characteristics of the lithium secondary battery under high voltage and high temperature conditions can be improved. For example, if the aluminum content of the coating layer is too high, a uniform coating layer may not be formed or the resistance may increase, resulting in reduced charge / discharge efficiency and reduced life characteristics. Conversely, if the aluminum content of the coating layer is too low, a coating layer of appropriate thickness may not be formed, resulting in reduced effect of suppressing side reactions with the electrolyte.
[0035] According to an embodiment, the coating layer may be in the form of a film that continuously surrounds the surface of the core particle, for example, in the form of a shell that surrounds the entire surface of the core particle. This is distinguished from a structure in which only a part of the surface of the core particle is partially coated. According to an embodiment, the coating layer may be formed in a form that entirely surrounds the surface of the core particle, but may be formed with a very thin and uniform thickness, so that the positive electrode active material does not increase in resistance, does not decrease in capacity, improves structural stability, effectively suppresses side reactions with the electrolyte, reduces the amount of gas generation under high voltage and high temperature conditions, and achieves long life characteristics.
[0036] The thickness of the coating layer is 30 nm to 200 nm, and may be, for example, 30 nm to 150 nm, 50 nm to 200 nm, 80 nm to 200 nm, or 100 nm to 200 nm. When the coating layer satisfies the above thickness range, the coating does not increase resistance or decrease capacity, improves the structural stability of the positive electrode active material, and effectively suppresses side reactions with the electrolyte. The thickness of the coating layer may be measured, for example, by TOF-SIMS, XPS, or EDS analysis, and the thickness range of the coating layer may be measured by TEM-EDS line profile.
[0037] According to an embodiment, the coating layer has a thickness of tens to hundreds of nanometers and is uniform. For example, the deviation of the coating layer thickness within one positive electrode active material particle may be 20% or less, 18% or less, or 15% or less. Here, the deviation of the coating layer thickness refers to the thickness of the coating layer within one positive electrode active material particle. The deviation of the coating layer thickness means, for example, that the thickness of 10 or more points is measured in an electron microscope image of a cross section of one positive electrode active material particle, the arithmetic average is calculated, and the absolute value of the difference between one data and the arithmetic average value is divided by the arithmetic average value and multiplied by 100. The deviation of the coating layer thickness satisfies the above range, which means that a coating layer of uniform thickness is well formed in the form of a film on the surface of the positive electrode active material particle, thereby improving the structural stability of the positive electrode active material, effectively suppressing side reactions with the electrolyte, and minimizing the increase in resistance and the decrease in capacity due to the coating.
[0038] The coating layer may include an aluminum compound having a layered structure. That is, the coating layer may include a lithium aluminum oxide having a layered structure, for example, LiAlO2. The coating layer having a layered structure is thinly and uniformly formed on the surface of the core particle, which can facilitate the movement of lithium and protect the core particle while increasing the capacity, thereby improving the life characteristics.
[0039] Meanwhile, the coating layer may further contain nickel, manganese, or a combination thereof in addition to aluminum. Nickel and manganese are contained in the core particles and flow in during the coating layer formation process, and the content thereof is not particularly limited. The coating layer according to an embodiment contains aluminum and selectively contains nickel and manganese, and can be called an aluminum-rich coating layer. The coating layer is formed with a thin and uniform thickness, and can improve the high voltage characteristics and life characteristics of the positive electrode active material.
[0040] Grain boundary coating part In the process of forming the coating layer, aluminum may be diffused into the core particles. Thus, the positive electrode active material according to an embodiment may further include a grain boundary coating portion containing aluminum located on the surface of the primary particle inside the secondary particle. Here, the secondary particle refers to the core particle, and the inside of the secondary particle refers to the entire inside except for the surface of the secondary particle, or may refer to a region from the surface of the secondary particle to about 60% of the radius in the direction toward the center of the secondary particle. The grain boundary coating portion is a concept distinct from the coating layer on the surface of the core particle, and refers to a coating portion formed on the surface of the primary particle located inside the core particle. The presence of the grain boundary coating portion can be confirmed by SEM-EDS analysis of the cross section of the positive electrode active material. By forming the aluminum grain boundary coating portion, the positive electrode active material is structurally more stabilized and the life characteristics are improved.
[0041] The aluminum content in the grain boundary coating portion is not particularly limited, and as an example, the aluminum content in the grain boundary coating portion may be less than the aluminum content in the coating layer.
[0042] The grain boundary coating portion may contain an aluminum compound having a layered structure, similar to the above-mentioned coating layer. That is, the grain boundary coating portion may contain a lithium aluminum oxide having a layered structure, such as LiAlO2. The formation of a grain boundary coating portion having a layered structure within the core particle promotes the movement of lithium, increases the capacity, improves the structural stability, and improves the life characteristics.
[0043] In addition, the grain boundary coating portion may further contain nickel, manganese, or a combination thereof in addition to aluminum. The grain boundary coating portion may also be referred to as an aluminum-rich coating portion.
[0044] The average particle size (D 50The average particle size is determined by measuring the size (diameter or major axis length) of 20 or more particles randomly in a scanning electron microscope image of the positive electrode active material to obtain a particle size distribution, and calculating the diameter (D) of the particle that occupies 50% of the cumulative volume in the particle size distribution. 50 When the average particle size of the positive electrode active material satisfies the above range, high capacity and long life can be achieved, and it is advantageous to form the coating layer according to an embodiment.
[0045] In the positive electrode active material according to an embodiment, the content of cobalt may be, for example, 0.01 mol % or less, 0.005 mol % or less, 0.001 mol % or less, for example, 0 mol % to 0.01 mol %, relative to 100 mol % of all metals excluding lithium. The positive electrode active material according to an embodiment may be, for example, a cobalt-free positive electrode active material.
[0046] In addition, the positive electrode active material according to an embodiment may be characterized in that it does not contain sodium. Although sodium ions can be generally used in a process for manufacturing a positive electrode active material, according to a manufacturing method described below, it is possible to form core particles with a stable structure and a coating layer with a uniform thickness without using sodium ions.
[0047] Method for producing positive electrode active material In one embodiment, a method for producing a positive electrode active material is provided, comprising: mixing a nickel-manganese-aluminum-based composite hydroxide and a lithium raw material, performing a first heat treatment to obtain a lithium nickel-manganese-aluminum-based composite oxide; introducing the obtained lithium nickel-manganese-aluminum-based composite oxide into a solution in which an aluminum raw material is mixed in an aqueous solvent, mixing, drying, and performing a second heat treatment to obtain a positive electrode active material. Here, the nickel content in the nickel-manganese-aluminum-based composite hydroxide is 60 mol% to 80 mol%, and the aluminum content is 1 mol% to 3 mol%, based on 100 mol% of the total metals in the positive electrode active material, and the aluminum content in the aluminum raw material is 0.1 mol% to 2 mol%, based on 100 mol% of the total metals in the positive electrode active material excluding lithium. The above-mentioned positive electrode active material can be produced by this method.
[0048] The nickel-manganese-aluminum composite hydroxide is a precursor of core particles, and may be in the form of secondary particles formed by agglomeration of a plurality of primary particles, and may contain no cobalt or a very small amount of cobalt, for example, a cobalt-free nickel-manganese-aluminum composite hydroxide. The nickel-manganese-aluminum composite hydroxide may be prepared by a conventional coprecipitation method.
[0049] A method for producing a positive electrode active material according to an embodiment is characterized in that, when producing core particles, aluminum is not further doped, and instead, an aluminum raw material is used when producing a precursor, thereby using a nickel-manganese-aluminum composite hydroxide in which aluminum is uniformly dispersed within the structure as a precursor. By using such a precursor, a positive electrode active material that does not contain cobalt and that stably maintains a layered structure even after repeated charging and discharging can be produced, and aluminum by-products and aluminum aggregates are not formed, thereby improving the capacity, efficiency characteristics, and life characteristics of the positive electrode active material.
[0050] The nickel content in the nickel-manganese-aluminum composite hydroxide is 60 mol% to 80 mol% relative to 100 mol% of the total metal, and may be, for example, 65 mol% to 80 mol%, 70 mol% to 80 mol%, 60 mol% to 79 mol%, 60 mol% to 78 mol%, or 60 mol% to 75 mol%. When the nickel content satisfies the above range, a high capacity can be achieved, and the structural safety can be improved even if the cobalt content is reduced. Such a composite hydroxide is distinguished from a high-nickel composite hydroxide having a nickel content of more than 80 mol%. The composite hydroxide according to one embodiment has different surface characteristics, such as the residual lithium content, pH, and shape on the surface, from the high-nickel composite hydroxide, making it difficult to apply the same coating method to both.
[0051] The manganese content in the nickel-manganese-aluminum composite hydroxide may be 10 mol% to 39 mol% relative to 100 mol% of the total metal, and may be 10 mol% to 35 mol%, 10 mol% to 30 mol%, 10 mol% to 29 mol%, 15 mol% to 39 mol%, 20 mol% to 39 mol%, 20 mol% to 30%, etc. In addition, the aluminum content in the nickel-manganese-aluminum composite hydroxide may be 1 mol% to 3 mol% relative to 100 mol% of the total metal, and may be, for example, 1 mol% to 2.5 mol%, 1 mol% to 2 mol%, or 1 mol% to 1.9 mol%. When the manganese and aluminum contents in the composite hydroxide satisfy the above ranges, respectively, high capacity can be realized and the structural safety of the positive electrode active material can be improved, and the production price can be reduced to improve the economic efficiency.
[0052] In the nickel-manganese-aluminum composite hydroxide, the cobalt content may be 0.01 mol% or less, 0.005 mol% or less, or 0.001 mol% or less, based on 100 mol% of the total metal. Such nickel-manganese-aluminum composite hydroxide can avoid the increase in unit price due to cobalt, making it economical, maximizing capacity, and improving structural stability.
[0053] An example of the nickel-manganese-aluminum composite hydroxide is represented by the following chemical formula 2. [Chemical formula 2] Ni x2 Mn y2 Al z2 M 2 w2 (OH)2 In chemical formula 2, 0.6≦x2≦0.8, 0.1≦y2≦0.39, 0.01 <z2≦0.03、0≦w2≦0.29、および0.9≦x2+y2+z2+w2≦1.1であり、M 2 is one or more elements selected from Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr.
[0054] The nickel-manganese-aluminum composite hydroxide is in the form of particles, and the average particle size (D 50 ) can be 10 μm to 18 μm, 11 μm to 16 μm, or 12 μm to 15 μm.
[0055] The nickel-manganese-aluminum composite hydroxide and the lithium raw material can be mixed at a molar ratio of 1:0.9 to 1:1.8, for example, at a molar ratio of 1:0.9 to 1:1.5 or 1:0.9 to 1:1.2.
[0056] The first heat treatment can be carried out in an oxygen atmosphere, for example, at a temperature range of 750° C. to 950° C., or 780° C. to 900° C., or 810° C. to 890° C., for 2 hours to 20 hours, or 4 hours to 12 hours.
[0057] The first heat treatment can produce a lithium nickel-manganese-aluminum composite oxide. The obtained composite oxide contains nickel at 60 mol% or more, for example, 60 mol% to 80 mol%, based on 100 mol% of all metals excluding lithium, and can contain no cobalt or a very small amount of 0.01 mol% or less. Such composite oxides have a significantly different content of residual lithium on the particle surface from existing nickel-based oxides of other compositions, such as lithium nickel-cobalt-manganese composite oxides and lithium nickel-cobalt-aluminum composite oxides, and many of the surface properties are different, so that it is impossible to form a good coating layer with a uniform film shape by using existing coating methods. In one embodiment, a method is provided for improving high voltage and high temperature properties by forming a uniform coating layer with a very thin thickness on the surface of a lithium nickel-manganese-aluminum composite oxide having a very small amount of cobalt and a nickel content of 60 mol% to 80 mol%.
[0058] In one embodiment, the lithium nickel-manganese-aluminum based composite oxide obtained by the first heat treatment is mixed with an aqueous solvent containing an aluminum raw material, and then dried and subjected to a second heat treatment to form a coating layer according to one embodiment. This can be considered as a kind of wet coating method.
[0059] The aqueous solvent may include distilled water, an alcohol-based solvent, or a combination thereof.
[0060] The aluminum raw material may include, for example, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof. As an example, the aluminum raw material may include aluminum sulfate, which is advantageous in forming a coating layer having a uniform thickness on the surface of the lithium nickel-manganese-aluminum composite oxide particles.
[0061] The aluminum raw material is a raw material for forming the coating layer, and the aluminum content in the aluminum raw material can be designed to be 0.1 mol% to 2 mol% with respect to 100 mol% of the total metals excluding lithium in the finally obtained positive electrode active material, for example, 0.2 mol% to 1.9 mol%, 0.3 mol% to 1.8 mol%, 0.5 mol% to 1.5 mol%, or 0.8 mol% to 1.3 mol%. By designing the content of the coating raw material within the above range, a coating layer having a thin thickness of tens to hundreds of nanometers and a uniform thickness can be formed, and the amount of gas generation of the lithium secondary battery under high voltage or high temperature driving conditions can be reduced, and high capacity and long life characteristics can be improved.
[0062] The solution in which the aluminum raw material is mixed with the aqueous solvent has a pH of 1.5 to 3.5, for example, 2.0 to 3.4, 2.5 to 3.3, 2.7 to 3.3, or 2.9 to 3.2. The lithium nickel-manganese-aluminum composite oxide can be added to the aqueous solvent in which the aluminum raw material is mixed and mixed for about 5 to 80 minutes, or 5 to 60 minutes, or 5 to 40 minutes. The pH of the mixed solution after stirring is 4.5 to 8.5, for example, 5.0 to 8.0, 5.5 to 7.5, or 6.0 to 7.0. When such conditions are satisfied, it is advantageous for a coating layer of uniform thickness to be formed.
[0063] Drying after the mixing step can be understood as a step of removing the solvent, and can be carried out at, for example, 40°C to 240°C, 100°C to 220°C, or 150°C to 200°C.
[0064] The second heat treatment can be understood as a process for forming a coating layer, and can be carried out, for example, in an oxygen atmosphere at a temperature range of 700°C to 850°C, 750°C to 840°C, or 800°C to 830°C for 2 hours to 20 hours, or 3 hours to 10 hours. The second heat treatment temperature can be lower than the first heat treatment temperature, and the second heat treatment time is preferably the same as or shorter than the first heat treatment time. By carrying out the second heat treatment under such conditions, a desired coating layer can be obtained.
[0065] positive electrode In one embodiment, the positive electrode includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer including the positive electrode active material described above. The positive electrode active material layer may further include other types of positive electrode active materials in addition to the positive electrode active materials described above. The positive electrode active material layer may also optionally include a binder, a conductive material, or a combination thereof.
[0066] According to one embodiment, the loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 For example, 10 mg / cm 2 ~30mg / cm 2 or 10 mg / cm 2 ~20mg / cm 2 In addition, the density of the positive electrode active material layer in the final rolled positive electrode may be 3.3 g / cc to 3.7 g / cc, for example, 3.3 g / cc to 3.6 g / cc or 3.4 g / cc to 3.58 g / cc. When the positive electrode active material according to an embodiment is applied, it is advantageous to achieve such a loading level and positive electrode density, and a positive electrode satisfying the above-mentioned ranges of loading level and positive electrode density is suitable for realizing a lithium secondary battery with high capacity and high energy density.
[0067] binder The binder serves to make the positive electrode active material particles adhere well to each other and to make the positive electrode active material adhere well to the current collector. Representative examples of the binder include, but are not limited to, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, nylon, etc.
[0068] Conductive material The conductive material is used to impart electrical conductivity to the electrodes, and any material that does not cause a chemical change in the battery that is constructed and is electronically conductive can be used. Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials containing copper, nickel, aluminum, silver, and the like in the form of metal powder or metal fibers; conductive polymers such as polyphenylene derivatives; and mixtures thereof.
[0069] The content of the binder and the conductive material may be 0.5% by weight to 5% by weight, respectively, relative to 100% by weight of the positive electrode active material layer.
[0070] The positive electrode current collector can be made of Al, but is not limited to this.
[0071] Lithium secondary battery In one embodiment, a lithium secondary battery is provided that includes the positive electrode, the negative electrode, and the electrolyte described above.
[0072] Lithium secondary batteries can be classified into cylindrical, square, pouch, coin, etc. types according to their shapes. FIG. 1 is a schematic diagram showing a lithium secondary battery according to an embodiment. Referring to FIG. 1, a lithium secondary battery 100 may include an electrode assembly 40 having a separator 30 between a positive electrode 10 and a negative electrode 20, and a case 50 in which the electrode assembly 40 is housed. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte (not shown).
[0073] The lithium secondary battery according to an embodiment may be capable of being charged at a high voltage or may be suitable for being driven at a high voltage. For example, the charging voltage of the lithium secondary battery may be 4.45 V or more, such as 4.45 V to 4.7 V, 4.45 V to 4.6 V, or 4.45 V to 4.55 V. By applying the positive electrode active material according to an embodiment, the lithium secondary battery may significantly reduce the amount of gas generated even when charged at a high voltage, and may realize high capacity and long life characteristics.
[0074] negative electrode The negative electrode can include a current collector and a negative electrode active material layer located on the current collector, the negative electrode active material layer including a negative electrode active material and can further include a binder, a conductive material, or a combination thereof.
[0075] negative electrode active material The negative electrode active material includes a material capable of reversibly inserting / extracting lithium ions, lithium metal, a lithium metal alloy, a material capable of being doped and dedoped with lithium, or a transition metal oxide.
[0076] The material capable of reversibly inserting / extracting lithium ions is a carbon-based negative electrode active material, and may include, for example, crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, and calcined coke.
[0077] As the alloy of the lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn can be used.
[0078] As the substance capable of doping and undoping lithium, an Si-based negative electrode active material or an Sn-based negative electrode active material can be used. As the Si-based negative electrode active material, silicon, a silicon-carbon composite, SiOx (0 < x < 2), an Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, for example, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof), or a combination thereof can be used. As the Sn-based negative electrode active material, Sn, SnO2, an Sn alloy, or a combination thereof can be used.
[0079] The silicon-carbon composite can be a composite of silicon and amorphous carbon. The average particle diameter (D 50 ) of the silicon-carbon composite particles can be, for example, 0.5 μm to 20 μm. According to one embodiment, the silicon-carbon composite can be in a form in which silicon particles and amorphous carbon are coated on the surface of the silicon particles. For example, it can include secondary particles (cores) formed by granulating primary silicon particles and an amorphous carbon coating layer (shell) located on the surface of the secondary particles. The amorphous carbon can also be located between the primary silicon particles, and for example, the primary silicon particles can be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.
[0080] The silicon-carbon composite may further contain crystalline carbon. For example, the silicon-carbon composite may include a core containing crystalline carbon and silicon particles, and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. Examples of the amorphous carbon include soft carbon, hard carbon, mesophase pitch carbide, and calcined coke.
[0081] When the silicon-carbon composite contains silicon and amorphous carbon, the content of silicon may be 10% to 50% by weight based on 100% by weight of the silicon-carbon composite, and the content of amorphous carbon may be 50% to 90% by weight. When the composite contains silicon, amorphous carbon, and crystalline carbon, the content of silicon may be 10% to 50% by weight, the content of crystalline carbon may be 10% to 70% by weight, and the content of amorphous carbon may be 20% to 40% by weight based on 100% by weight of the silicon-carbon composite.
[0082] In addition, the thickness of the amorphous carbon coating layer may be 5 nm to 100 nm. The average particle diameter (D 50 ) of the silicon particles (primary particles) may be 10 nm to 1 μm, or 10 nm to 200 nm. The silicon particles may exist alone as silicon, or in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon may be represented by SiO x (0 < x < 2). At this time, the atomic content ratio of Si:O indicating the degree of oxidation may be 99:1 to 33:67. In this specification, unless otherwise defined, the average particle diameter (D 50 ) means the diameter of the particle with a cumulative volume of 50% by volume in the particle size distribution.
[0083] The Si-based negative electrode active material or the Sn-based negative electrode active material can be used by mixing with a carbon-based negative electrode active material. When the Si-based negative electrode active material or the Sn-based negative electrode active material is mixed with the carbon-based negative electrode active material, the mixing ratio may be 1:99 to 90:10 by weight.
[0084] binder The binder serves to adhere the negative active material particles to each other and to the current collector well. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.
[0085] Non-aqueous binders include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymers, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or combinations thereof.
[0086] The water-based binder may be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0087] When an aqueous binder is used as the negative electrode binder, a cellulose-based compound capable of imparting viscosity may be further included. As the cellulose-based compound, one or more of carboxymethylcellulose, hydroxypropylmethylcellulose, methylcellulose, or alkali metal salts thereof may be mixed and used. As the alkali metal, Na, K, or Li may be used.
[0088] The dry binder can be a fiberizable polymeric material such as polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.
[0089] Conductive material The conductive material is used to impart electrical conductivity to the electrodes, and may be any material that does not cause chemical changes in the battery and is electronically conductive. Specific examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials in the form of metal powder or metal fibers, including copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; and mixtures thereof.
[0090] The content of the negative electrode active material may be 95% to 99.5% by weight relative to 100% by weight of the negative electrode active material layer, and the content of the binder may be 0.5% to 5% by weight relative to 100% by weight of the negative electrode active material layer. For example, the negative electrode active material layer may contain 90% to 99% by weight of the negative electrode active material, 0.5% to 5% by weight of the binder, and 0.5% to 5% by weight of the conductive material.
[0091] Current collector The negative electrode current collector can include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or alloys thereof, and can be in foil, sheet, or foam form. The thickness of the negative electrode current collector can be, for example, 1 μm to 20 μm, 5 μm to 15 μm, or 7 μm to 10 μm.
[0092] electrolyte The electrolyte for a lithium secondary battery can be, by way of example, an electrolytic solution, which can include a non-aqueous organic solvent and a lithium salt.
[0093] The non-aqueous organic solvent serves as a medium through which the ions involved in the electrochemical reactions of the battery can migrate. The non-aqueous organic solvent may be a carbonate-, ester-, ether-, ketone-, or alcohol-based solvent, an aprotic solvent, or a combination thereof.
[0094] Examples of the carbonate solvent include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. Examples of the ester solvent include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc. Examples of the ether solvent include dibutyl ether, tetraglyme, diglyme, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, and tetrahydrofuran. Examples of the ketone solvent include cyclohexanone. Examples of the alcohol solvent include ethyl alcohol and isopropyl alcohol. Examples of the aprotic solvent include nitriles such as R-CN (R is a straight-chain, branched, or cyclic hydrocarbon group having 2 to 20 carbon atoms, and may contain a double bond, an aromatic ring, or an ether group); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane and 1,4-dioxolane; and sulfolanes.
[0095] The non-aqueous organic solvent may be used alone or in combination of two or more kinds. When using in combination of two or more kinds, the mixing ratio may be appropriately adjusted according to the desired battery performance, which is widely understood by those working in the field.
[0096] When a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate can be mixed and used, and the cyclic carbonate and the chain carbonate can be mixed in a volume ratio of 1:1 to 1:9.
[0097] The non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent. For example, the carbonate solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of 1:1 to 30:1.
[0098] The electrolyte may further contain a vinyl ethyl carbonate, vinylene carbonate or ethylene carbonate based compound to improve the battery life.
[0099] Representative examples of the ethylene carbonate-based compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0100] Lithium salts are substances that dissolve in organic solvents and act as a source of lithium ions in the battery to enable basic lithium secondary battery operation and facilitate the movement of lithium ions between the positive and negative electrodes. Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F2y+1 SO2) (x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), lithium difluorooxalate borate (LiDFOB), and lithium bis(oxalate)borate (LiBOB).
[0101] The lithium salt is preferably used at a concentration within the range of 0.1 M to 2.0 M. If the lithium salt concentration is within the above range, the electrolyte has appropriate ion conductivity and viscosity, and therefore can exhibit excellent performance and allow lithium ions to migrate effectively.
[0102] Separator Depending on the type of lithium secondary battery, a separator may be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers of these may be used, and it is of course possible to use a mixed multilayer film such as a two-layer separator of polyethylene / polypropylene, a three-layer separator of polyethylene / polypropylene / polyethylene, or a three-layer separator of polypropylene / polyethylene / polypropylene.
[0103] The separator may include a porous substrate and a coating layer including an organic material, an inorganic material, or a combination thereof located on one or both sides of the porous substrate.
[0104] The porous substrate may be a polymer membrane formed of any one polymer selected from polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate and polybutylene terephthalate, polyacetal, polyamide, polyimide, polycarbonate, polyether ketone, polyaryl ether ketone, polyetherimide, polyamide imide, polybenzimidazole, polyethersulfone, polyphenylene oxide, cyclic olefin copolymer, polyphenylene sulfide, polyethylene naphthalate, glass fiber, Teflon, and polytetrafluoroethylene, or a copolymer or mixture of two or more of these polymers.
[0105] The porous substrate can have a thickness of about 1 μm to 40 μm, for example, 1 μm to 30 μm, 1 μm to 20 μm, 5 μm to 15 μm, or 10 μm to 15 μm.
[0106] The organic material may include a (meth)acrylic copolymer including a first structural unit derived from (meth)acrylamide, a structural unit derived from (meth)acrylic acid or a (meth)acrylate, and a second structural unit including at least one of a structural unit derived from (meth)acrylamidosulfonic acid or a salt thereof.
[0107] The inorganic material may include, but is not limited to, inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof. The average particle size (D 50 ) may be 1 nm to 2000 nm, for example, 100 nm to 1000 nm, or 100 nm to 700 nm.
[0108] The organic material and the inorganic material may be mixed in one coating layer, or may be stacked in a coating layer including an organic material and a coating layer including an inorganic material.
[0109] The thickness of each of the coating layers may be from 0.5 μm to 20 μm, for example, from 1 μm to 10 μm, or from 1 μm to 5 μm.
[0110] Examples of the present invention and comparative examples are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.
[0111] Example 1 1. Manufacturing of positive electrode active material Ni 0.75 Mn 0.23 Al 0.02 (OH)2 and LiOH were mixed in a molar ratio of 1:1 and subjected to a first heat treatment at 850°C for 8 hours in an oxygen atmosphere to obtain a compound with the composition LiNi 0.75 Mn 0.23 Al 0.02 O2 and the average particle size (D 50 A composite oxide in the form of secondary particles having a particle size of about 14 μm was produced.
[0112] After mixing aluminum sulfate into a distilled water solvent, the composite oxide prepared was added and mixed for 20 to 60 minutes. At this time, the aluminum content in the aluminum sulfate was designed to be 1.0 mol% relative to 100% by weight of the total metals excluding lithium in the final positive electrode active material. After removing the solvent from the mixed solution and drying at 190°C, a second heat treatment was performed at 825°C for 8 hours in an oxygen atmosphere to prepare the final positive electrode active material.
[0113] 2. Manufacturing of lithium secondary batteries 98.5 wt% of the prepared positive electrode active material, 1.0 wt% of polyvinylidene fluoride binder, and 0.5 wt% of carbon nanotube conductive material were mixed to prepare a positive electrode active material layer slurry, which was then coated on an aluminum foil current collector, dried, and rolled to prepare a positive electrode. At this time, the loading level of the positive electrode active material layer was 10 mg / cm.2 and the density of the final rolled cathode was about 3.4 g / cc.
[0114] A negative electrode active material layer slurry was prepared by mixing 97.5 wt% graphite negative electrode active material, 1.5 wt% carboxymethyl cellulose, and 1 wt% styrene butadiene rubber in an aqueous solvent. The negative electrode active material layer slurry was coated on a copper foil current collector, and then dried and rolled to prepare a negative electrode.
[0115] A polytetrafluoroethylene separator was used, and a lithium secondary battery was fabricated in a conventional manner using an electrolyte solution prepared by dissolving 1M LiPF6 in a solvent mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 3:7.
[0116] Example 2 A positive electrode active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the positive electrode active material, the aluminum content in the aluminum sulfate was designed and mixed to be 0.5 mol % based on 100 wt % of the total metals excluding lithium in the final positive electrode active material.
[0117] Example 3 A positive electrode active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the positive electrode active material, the aluminum content in the aluminum sulfate was designed and mixed to be 1.5 mol % based on 100 wt % of the total metals excluding lithium in the final positive electrode active material.
[0118] Example 4 A positive electrode active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that in the preparation of the positive electrode active material, the aluminum content in the aluminum sulfate was designed and mixed to be 2.0 mol % based on 100 wt % of the total metals excluding lithium in the final positive electrode active material.
[0119] Comparative Example 1 Ni 0.75 Mn 0.25(OH)2, LiOH and Al2O3 were mixed in a molar ratio of 1:1:0.02 and heat-treated in an oxygen atmosphere at 850℃ for 8 hours to obtain a composition of LiNi 0.75 Mn 0.23 Al 0.02 O2 and the average particle size (D 50 A lithium secondary battery was manufactured in substantially the same manner as in Example 1, except that the aluminum-doped composite oxide was used as a positive electrode active material.
[0120] Comparative Example 2 Ni 0.75 Mn 0.25 Al 0.02 (OH)2 and LiOH were mixed in a 1:1 molar ratio and heat-treated in an oxygen atmosphere at 850°C for 8 hours to obtain a composition of LiNi 0.75 Mn 0.23 Al 0.02 O2 and the average particle size (D 50 A lithium secondary battery was manufactured in substantially the same manner as in Example 1, except that the aluminum-doped composite oxide was used as a positive electrode active material.
[0121] Comparative Example 3 A positive electrode active material was prepared in a manner substantially similar to that of Example 1, except that the aluminum coating was performed in a dry manner. 0.75 Mn 0.23 Al 0.02 A composite oxide in the form of secondary particles, O2, and aluminum oxide powder were mixed and heat-treated in an oxygen atmosphere at 825°C for 8 hours to prepare an Al-coated cathode active material in a dry manner. A lithium secondary battery was prepared in substantially the same manner as in Example 1, except that the cathode active material was used.
[0122] Comparative Example 4 The composition is LiNi 0.94 Co 0.03 Al 0.03 O2 and the average particle size (D 50A lithium secondary battery was manufactured in substantially the same manner as in Example 1, except that a composite oxide in the form of secondary particles having a particle size of about 14 μm was used as a positive electrode active material.
[0123] Comparative Example 5 A positive electrode active material was prepared by performing Al wet coating in the same manner as in Example 1 using the composite oxide of Comparative Example 4. A lithium secondary battery was prepared in substantially the same manner as in Example 1, except that the positive electrode active material was used.
[0124] Comparative Example 6 A positive electrode active material and a lithium secondary battery were manufactured in substantially the same manner as in Example 1, except that the aluminum content in the aluminum sulfate was designed to be 3.0 mol % based on 100 wt % of the total metals excluding lithium in the final positive electrode active material.
[0125] The design details of the positive electrode active materials in Examples 1 to 4 and Comparative Examples 1 to 6 are briefly shown in Table 1 below.
[0126] Evaluation Example 1: Comparison between Comparative Example 1 and Comparative Example 2 FIG. 2 shows an SEM image of the positive electrode active material of Comparative Example 1, and FIG. 3 shows an SEM image of the positive electrode active material of Comparative Example 2. Comparative Example 1 is a case where lithium nickel-manganese-aluminum oxide is prepared by further doping aluminum after synthesizing lithium nickel-manganese oxide. Referring to FIG. 2, it was found that the surface of the secondary particles of the positive electrode active material is not uniform, and aluminum by-products are formed as shown by the circle. Meanwhile, Comparative Example 2 is a case where lithium nickel-manganese-aluminum oxide is prepared in which aluminum is distributed in a uniform concentration in the secondary particles by using nickel-manganese-aluminum hydroxide as a precursor. Referring to FIG. 3, it was found that a spherical positive electrode active material with a very uniform surface of the secondary particles was successfully synthesized, and no aluminum by-products were formed. It can be understood that the examples use such Comparative Example 2 as a base material.
[0127] Evaluation example 2: Coating layer comparison 4 to 9 show SEM-EDS images of cross sections of the positive electrode active materials of Examples 1 to 4, Comparative Example 3, and Comparative Example 5, respectively. In the figures, the highlighted parts indicate aluminum. An SEM image of the surface of the positive electrode active material of Comparative Example 5 is shown in FIG.
[0128] It can be seen that the positive electrode active materials of Examples 1 to 4 shown in Figs. 4 to 7 successfully formed a very thin aluminum coating layer of uniform thickness on the surface of the secondary particles, forming a kind of core-shell structure. Meanwhile, referring to Fig. 8, in the case of Comparative Example 3 in which the dry coating method was applied, it was found that aluminum was irregularly aggregated on the surface of the secondary particles, and a coating layer surrounding the secondary particles was not formed. Also, referring to Figs. 9 and 10, in the case of Comparative Example 5 in which nickel-cobalt-aluminum oxide with a nickel content of 94 mol% was used as the base material and the same coating method as in the Examples was applied, it was found that aluminum was unevenly aggregated on the surface of the secondary particles, and a coating layer surrounding the secondary particles was not formed. It is understood that the positive electrode active material of Comparative Example 5 has a different composition from the Examples, and the residual lithium content and pH conditions on the surface of the composite oxide are different, so that a uniform coating layer is not formed even if the coating method of the Examples is applied.
[0129] Evaluation Example 3: Analysis of the coating layer and grain boundary coating part of the embodiment FIG. 11 is a TOF-SIMS depth profile for the positive electrode active material of Example 1, which is a graph showing how the ratio of the aluminum content to the nickel content changes from the surface to the inside of the secondary particles.
[0130] Fig. 12 is a TEM image of a cross section of the positive electrode active material of Example 1, and Fig. 13 is an enlarged image of the area indicated by a square in Fig. 12. Fig. 14 is an image in which oxygen, aluminum, manganese, and nickel are highlighted from the left by EDS analysis of the TEM image of Fig. 13. Fig. 15 is an EDS line profile showing the change in the oxygen, aluminum, manganese, and nickel contents in the direction of the arrows shown in Figs. 13 and 14.
[0131] 11 to 15, it can be seen that in the positive electrode active material according to Example 1, a thin and uniform Al coating layer having a thickness of about 30 nm to 200 nm is formed on the surface of the core particle.
[0132] The leftmost image in FIG. 16 is a TEM image of the cross section of the positive electrode active material of Example 1, which is an enlarged view of a primary particle located at the outermost shell of a secondary particle. The four images on the right of FIG. 16 are TEM-EDS images, which highlight O, Al, Mn, and Ni from the left. FIG. 17 is an EDS line profile showing the change in the content of O, Al, Mn, and Ni in the direction of the arrow shown in FIG. 16. Referring to FIG. 16 and FIG. 17, it can be seen that the interface of the primary particle located at the outermost shell of the secondary particle is also coated with Al, that is, a grain boundary coating portion is formed.
[0133] FIG. 18 is a TEM image of the cross section of the positive electrode active material of Example 1, and FIG. 19 is an enlarged photograph (left) of Area 1 in FIG. 18 and an image (right) of aluminum highlighted by EDS analysis. FIG. 20 is an enlarged photograph (left) of Area 2 in FIG. 18 and an EDS analysis image (right), and FIG. 21 is an enlarged photograph (left) of Area 3 in FIG. 18 and an EDS analysis image (right). In FIG. 18, the directions toward Area 1, Area 2, and Area 3 are directions from the inside of the core particle to the surface. Referring to FIG. 18 to FIG. 21, it can be seen that an Al grain boundary coating portion is formed at the interface of the primary particle at any position, including the inside of the core particle.
[0134] FIG. 22 is a TEM-EDS image of a primary particle in the outermost shell of a secondary particle in a cross section of the positive electrode active material of Example 1, in which the highlighted portion indicates aluminum. FIG. 23 shows a TEM analysis image of the portion indicated by the arrows (1) to (6) in FIG. 22. In FIG. 23, the positions (1) to (4) can be said to be the surface of the secondary particle, and therefore are positions where an aluminum coating layer can be confirmed, the position (5) is the inside of the primary particle, and the position (6) is a position where an aluminum grain boundary coating portion can be confirmed between the primary particles, that is, as a grain boundary. Referring to FIG. 23, a layered structure is observed at all positions, including the surface of the secondary particle, the inside of the primary particle, and the grain boundary. In other words, it is analyzed that both the coating layer and the grain boundary coating portion have a layered structure, and therefore, it is confirmed that the coating layer and the grain boundary coating portion contain layered lithium aluminum oxide, for example, LiAlO2.
[0135] Evaluation example 4: Evaluation of electrochemical properties The lithium secondary batteries produced in Examples 1 to 4 and Comparative Examples 1 to 6 were initially charged and discharged by charging at a constant current of 0.2 C at 25° C. up to an upper limit voltage of 4.45 V and at a constant voltage of 0.05 C, and then discharging at 0.2 C to an end voltage of 3.0 V. The initial charge capacity, initial discharge capacity, and the ratio of the latter to the former were efficiently calculated and shown in Table 1 below. Next, a cycle of charging at 1.0 C and discharging at 1.0 C in the voltage range of 3.0 V to 4.45 V at 45°C was repeated 25 times or more, and the ratio of the 25-cycle discharge capacity to the initial discharge capacity was calculated and shown in Table 1 below as a high-temperature life.
[0136] [Table 1]
[0137] First, comparing Comparative Example 1 and Comparative Example 2, it can be seen that the initial charge / discharge capacity is increased and the high-temperature life characteristics are improved in Comparative Example 2, in which aluminum is introduced as a precursor, compared to Comparative Example 1, in which aluminum is additionally doped. In the example, Comparative Example 2 is used as a base material and coating is performed by a specific method according to an embodiment to form a uniform coating layer, and it was confirmed that the initial charge / discharge capacity, efficiency, and high-temperature life characteristics can be improved simultaneously by coating with an Al content of 2 mol% or less.
[0138] Comparative Example 3 was a case where coating was performed using a type of dry method, and a uniform coating layer was not formed as in Evaluation Example 2, and therefore the high temperature life characteristics were significantly reduced compared to the Examples.
[0139] Comparative Examples 4 and 5 are cases where a lithium nickel-cobalt-aluminum oxide with a nickel content of 94 mol% is used, and it is analyzed that the high temperature life characteristics are lower than those of the Examples, and there is a problem of increased costs due to the use of cobalt. Comparative Example 5 is a case where the same coating method as in the Examples is applied to the base material of Comparative Example 4, and it was found that a uniform coating layer was not formed as in Evaluation Example 2, and as shown in Table 1, the initial charge / discharge capacity and efficiency were rather decreased. It is understood that if a uniform coating layer in the form of a shell surrounding the core is not formed, the charge / discharge capacity of the battery will decrease, the resistance will increase, and the life characteristics will also decrease or not be improved.
[0140] On the other hand, in Comparative Example 6, the same base material and coating method as in the Example were used, but the Al coating content was increased to 3 mol%, and it was analyzed that the initial charge / discharge capacity was significantly reduced and the initial charge / discharge efficiency was also reduced.
[0141] Although the preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concepts defined in the claims also fall within the scope of the present invention. [Explanation of symbols]
[0142] 100 Lithium secondary battery 10 positive electrode 20 negative electrode 30 Separator 40 Electrode assembly 50 cases
Claims
1. Core particles containing a lithium nickel-manganese-aluminum composite oxide, and a coating layer located on a surface of the core particle and containing aluminum; a nickel content of the core particle is 60 mol% to 80 mol%, an aluminum content of the core particle is 1 mol% to 3 mol%, and an aluminum content of the coating layer is 0.1 mol% to 2 mol%, relative to 100 mol% of all metals excluding lithium.
2. 2. The positive electrode active material according to claim 1, wherein the aluminum content of the coating layer is 0.5 mol % to 1.5 mol % based on 100 mol % of all metals excluding lithium.
3. The positive electrode active material according to claim 1 , wherein the coating layer is in the form of a shell that continuously surrounds the surface of the core particle.
4. The positive electrode active material according to claim 1 , wherein the coating layer has a thickness of 30 nm to 200 nm.
5. The positive electrode active material of claim 1 , wherein the coating layer has a thickness deviation of 20% or less within one positive electrode active material.
6. The positive electrode active material according to claim 1 , wherein the coating layer comprises an aluminum compound having a layered structure.
7. The coating layer is LiAlO 2 The positive electrode active material of claim 1 .
8. The positive electrode active material of claim 1 , wherein the coating layer further contains nickel, manganese, or a combination thereof.
9. The lithium nickel-manganese-aluminum composite oxide of the core particle is represented by chemical formula 1, [Chemical formula 1] Li a1 Ni x1 Mn y1 Al z1 M 1 w1 O 2-b1 X b1 In Chemical Formula 1, 0.9≦a1≦1.8, 0.6≦x1≦0.8, 0.1≦y1≦0.39, 0.01<z1≦0.03, 0≦w1≦0.29, 0.9≦x1+y1+z1+w1≦1.1, and 0≦b1≦0.1; M 1 is one or more elements selected from B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, and Zr, and X is one or more elements selected from F, P, and S.
10. The positive electrode active material according to claim 1 , wherein the aluminum concentration is uniform within the core particle.
11. 2. The positive electrode active material according to claim 1, wherein the lithium nickel-manganese-aluminum based composite oxide of the core is a cobalt-free compound.
12. 2. The positive electrode active material according to claim 1, wherein the content of cobalt is 0 mol % to 0.01 mol % relative to 100 mol % of all metals excluding lithium.
13. The positive electrode active material according to claim 1 , wherein the core particle is in the form of a secondary particle formed by agglomeration of a plurality of primary particles.
14. The positive electrode active material of claim 13 , further comprising a grain boundary coating portion located on a surface of the primary particle inside the secondary particle and containing aluminum.
15. The positive electrode active material according to claim 14 , wherein the grain boundary coating portion includes an aluminum compound having a layered structure.
16. The grain boundary coating portion is LiAlO 2 The positive electrode active material of claim 14 .
17. The positive electrode active material according to claim 14 , wherein the grain boundary coating further contains nickel, manganese, or a combination thereof.
18. The positive electrode active material according to claim 14 , wherein the content of aluminum in the grain boundary coating portion is less than the content of aluminum in the coating layer.
19. The average particle size (D 50 2. The positive electrode active material according to claim 1, wherein the average particle diameter is 10 μm to 18 μm.
20. The cathode active material of claim 1 , wherein the cathode active material does not contain sodium.
21. A nickel-manganese-aluminum-based composite hydroxide and a lithium raw material are mixed and subjected to a first heat treatment to obtain a lithium nickel-manganese-aluminum-based composite oxide; The lithium nickel-manganese-aluminum composite oxide thus obtained is introduced into a solution in which an aluminum raw material is mixed in an aqueous solvent, and then the resulting mixture is dried and subjected to a second heat treatment to obtain a positive electrode active material; In the nickel-manganese-aluminum based composite hydroxide, the nickel content is 60 mol% to 80 mol% and the aluminum content is 1 mol% to 3 mol% relative to 100 mol% of the total metals; The method for producing a positive electrode active material, wherein the aluminum content in the aluminum raw material is 0.1 mol % to 2 mol % relative to 100 mol % of all metals excluding lithium in the positive electrode active material.
22. The method for producing a positive electrode active material according to claim 21, wherein the aluminum content in the aluminum raw material is 0.5 mol% to 1.5 mol% relative to 100 mol% of all metals excluding lithium in the positive electrode active material.
23. 22. The method of claim 21, wherein the aluminum source comprises aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum hydroxide, or a combination thereof.
24. The method for producing a positive electrode active material according to claim 21, wherein the solution in which the aluminum raw material is mixed in the aqueous solvent has a pH of 1.5 to 3.
5.
25. The method for producing a positive electrode active material according to claim 21, wherein the lithium nickel-manganese-aluminum-based composite oxide is added to the solution obtained by mixing the aluminum raw material in the aqueous solvent and mixed for 5 minutes to 80 minutes, and the pH of the solution after mixing is 4.5 to 8.
5.
26. The method for producing a positive electrode active material according to claim 21, wherein the drying is carried out at 40°C to 240°C.
27. The first heat treatment is carried out at 750°C to 950°C, The method for producing a positive electrode active material according to claim 21, wherein the second heat treatment is performed at 700°C to 850°C.
28. A positive electrode current collector, and a positive electrode active material layer located on the positive electrode current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 20.
29. The loading level of the positive electrode active material layer is 10 mg / cm 2 ~40mg / cm 2 30. The positive electrode of claim 28,
30. 29. The positive electrode of claim 28, wherein the positive electrode active material layer has a density of 3.3 g / cc to 3.7 g / cc.
31. 29. The positive electrode of claim 28 . a negative electrode, and A lithium secondary battery comprising an electrolyte.
32. 32. The lithium secondary battery according to claim 31, having a charging voltage of 4.45 V or higher.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery and its manufacture, positive electrode for lithium secondary battery using the positive electrode active material and its manufacture, and lithium secondary battery using the positive electrode and its manufacture
JP2000223122A
Cobalt-free positive electrode material and its preparation method, as well as lithium-ion battery positive electrode and lithium battery
JP2022553657A
Non-aqueous electrolyte secondary battery
WO2022196040A1
